A INFLUÊNCIA DAS MULHERES CLÂNICAS NO PENSAMENTO PROFÉTICO DO PÓS-EXÍLIO. UM ESTUDO DE ISAÍAS 57,1-21. - Kanashiro, Helder Blessa (2015)
In this work on The Influence of Clan Women in Prophetic Thought Post-Exile. A Study of Isaiah 57.1 to 21, we propose a search for fundamentally demonstrate who the three groups of clan women who appear in Isaiah 57.3 to 9, namely: hn+n>[o (sorceress) aEßnm. (Adultery, meaning adulterous - tp,a(nm) and hnAz (prostitute) And so develop that influence had in prophecy, in the post-exilic period To such a task we used two methods: the first, one diachronic method in which the text demonstrated a very negative view of these women, as the backdrop would be established where the text is strong patriarchal influence. But by applying a second, the synchronic and intertextual method, the result showed different because the set of texts which are included, namely: Isa from 56.1 to 12, 58.1 to 14, and from 61.1 to 11, inclusive demonstrate the program Thus, in Isa 56.3-4 - rkªNEh;-!B, (foreign son) and syrIêSh; (eunuchs) are admitted to the community; in Isaiah 58, 1 - bqoß[]y: tybeîl.W (and the house of Jacob), this house represented by a group of men is reprimanded because of fasting; and Isaiah 61.5 to 6 - ~yrIêz (strangers) and rkênE ynEåb.W (and foreign children), they are ones who feed the community. Due to this, there was a chance that a negative view of them could not be accepted within an inclusive project. However the question must be answered. Leave to do a mapping of the clan way of life in Genesis, a set of texts that speak mainly family/ clan. As we study some mythical mothers: Havah, Sarah, Hagar, daughters of Lot and Tamar, and compare them with those of Isaiah 57.3 to 9, many of the characteristics show similar. So we realize that all these women by having clan kingdom animal and plant knowledge, exerted influence on the life and death of families/clans, so they had to be fought by groups of men over time. Yet another important feature in the post-exile, is the movement that families/clans perform, but this exit is always loaded with plenty of fertility and conflict resolution solidarity. We should be in the prophecy, as to crystallize a negative text against a group of women, in fact we are denouncing violence against them.